[Swallow the bitter pill ; So long Pong ; Gary V. [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
An interview with foreign exchange dealers on dollar black market that determines much of the economic activity in these times of economic crisis. Batibot, Philippine TV's Sesame Street is about to lose Pong Pagong and Kiko Matsing, two characters created for it by the U.S. Company. A signature campaign hopes to keep them here. Interview with Gary V. on his latest concert Major Impact."